2012
DOI: 10.1177/0734371x11433881
|View full text |Cite
|
Sign up to set email alerts
|

Do Coworkers Make the Service Customer? A Field Study in the Public Sector

Abstract: This article examines whether relationships among colleagues are related to commitment to the customer and intention to leave the employer. Using a sample (N = 228) of public employees in contact with citizens (customers), the data showed that exchange process among colleagues enhances commitment to the customer and diminishes intention to leave through intention to help colleagues. Results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…The most theory used was the Social Exchange Theory (e.g. Paillé, 2013; Chan and Mak, 2012). This frequency of use might be related to the fact that, it is among the most influential conceptual paradigms for understanding workplace behavior, relationships and reciprocity that go beyond contractual agreement behaviors, and ultimately resulting in positive exchanges (Cropanzano and Mitchell, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The most theory used was the Social Exchange Theory (e.g. Paillé, 2013; Chan and Mak, 2012). This frequency of use might be related to the fact that, it is among the most influential conceptual paradigms for understanding workplace behavior, relationships and reciprocity that go beyond contractual agreement behaviors, and ultimately resulting in positive exchanges (Cropanzano and Mitchell, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, healthcare professionals must develop a patient-centered care approach because each patient shows a combination of special characteristics such as illness, pain, uncertainty, or fear that make him or her a unique challenge (Keeling et al , 2018). Healthcare professionals have to offer service quality without faults or errors as much as possible, often with limited resources (Thanacoody et al , 2014), knowing that patients expect higher service quality (Paillé, 2013). Additionally, the intense, direct contact between professionals and patients (Schaufeli, 2007) and the coexistence of high rates of mortality (Rizo-Baeza et al , 2018) may cause professionals to develop negative feelings toward their work (Maslach and Leiter, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The public sector employs disproportionately more women than men (Bernhardt & Dresser, 2002; Gornick & Jacobs, 1998; Llorens et al, 2008), and due to a lowered potential for gender-based discrimination and greater opportunities to achieve work–family balance, women may receive more benefits from public-sector employment than from employment in the private sector (Benditt, 2015; Buelens & Van den Broeck, 2007; Bureau of Labor Statistics, 2016; Llorens et al, 2008; Moynihan & Landuyt, 2008). Furthermore, female public-sector workers have been shown to have lower levels of turnover intention relative to men (Moynihan & Landuyt, 2008; Paillé, 2013). For example, a recent survey of U.S. federal employees found that women show greater commitment than men to holding a federal job (Wynen et al, 2013).…”
Section: Gender and Affective Organizational Commitmentmentioning
confidence: 99%